Diagnostico ambiental bacteriológico de vertidos generados en la Planta de tratamiento Pagua cantón El Guabo y planteamiento de medidas correctoras - Balarezo Peñafiel, Bryan Felipe; Zambrano Bermeo, Diego Armando (Machala, 2021)
Wastewater discharges that do not have optimal treatment are the main source of contamination to bodies of water such as rivers, estuaries, streams and streams, reaching the sea as their final destination, causing various problems in nature's cycles such as people's health. The wastewater treatment plant of the Pagua Site is managed by the Public Company of Potable Water and Sewerage of the El Guabo Canton and the Department of Environmental Management, the structure has been operating for 12 years together with the sewerage of the place, the benefited families are around than 400 covering the entire sector. The WWTP currently owns by: • Pumping stations. - They have 3-inch pumps and have a basket that is used for the collection of large waste, in the same way, it has a system of valves that fulfill the function of preventing the residual water from returning once the filters are completely full. • Biological filters. - It is divided into four chambers, the two main chambers are where the water passes, in the third chamber we will find sand, gravel and ball stone and in the last chamber the water will come out with less dissolved organic matter. • Cistern. - Place where the water is stored before being directed towards the two main systems. • Effluent. - It is the discharge that is deposited or directed towards the Pagua river. For the Bacteriological Environmental Diagnosis, a "quali-quantitative" approach was used, field research, applied, documentary and correlational, in addition to the application of a laboratory analysis of the parameters "Total Coliforms, Fecal Coliforms and Escherichia Coli" to determine the microbiological state in which the discharges from the wastewater treatment plant of Cantón El Guabo are found. Through various research techniques and instruments such as observation, interviews with various EPAAGUA and DGA authorities, the diagnosis could be optimized. As a final diagnosis, it was determined that the structure of the treatment plant does not fully fulfill its function in terms of water purification due to the fact that the capacity does not supply the family number of the site, the treatment is not working for the microbiological parameters, exceeding in Fecal Coliforms with 2.5 times, Total Coliforms with 24,097 times, however, with Escherichia Coli it is within the range. Taking into account the Unified Text of Secondary Environmental Legislation, Regulation of Water Quality and Control of Discharges AG-CC-01 of the Dominican Republic and Legal Regime of the Reuse of Purified Waters of Spain. As an integrating proposal, a possible Design of a chlorination tank / disinfection system was projected as a final treatment, in order to reduce microbiological loads. A scheme was proposed that goes according to the area of the treatment plant and the amount of the residual flow, in addition to the retention time that the residual water will have, thus reducing the LMP, obtaining as a final product a treated water free of contamination.
Las descargas de aguas residuales que no disponen de un tratamiento optimo son la principal fuente de contaminación hacia los cuerpos de aguas como ríos, esteros, arroyos y riachuelos, llegando como destino final el mar, provocando varios problemas en los ciclos de la naturaleza como a la salud de las personas. La planta de tratamiento de aguas residuales del Sitio Pagua está administrada por la Empresa Pública de Agua Potable y Alcantarillado del Cantón El Guabo y el Departamento de Gestión Ambiental, la estructura tiene 12 años funcionando junto con el alcantarillado del lugar, las familias beneficiadas son alrededor de 400 que comprende todo el sector. La PTAR posee actualmente por: • Estaciones de bombeo. - cuentan con bombas de 3 pulgadas y cuentan con una canastilla que sirve para la recolección de desechos de gran tamaño, de igual manera cuenta con un sistema de válvulas que cumplen la función de evitar que el agua residual regrese una vez que los filtros estén completamente llenos. • Filtros biológicos. - se divide en cuatro cámaras, las dos cámaras principales son en donde el agua pasa, en la tercera cámara encontraremos arena, grava y piedra bola y en la última cámara el agua saldrá con menos materia orgánica disuelta. • Cisterna. - Lugar donde se almacena el agua antes de ser dirigida hacia los dos principales sistemas. • Efluente. - Es el vertido que está depositado o dirigido hacia el rio Pagua. Para el Diagnóstico Ambiental Bacteriológico, se utilizó un enfoque “cuali-cuantitativo”, investigación de campo, aplicada, documental y correlacional, además de la aplicación de un análisis de laboratorio de los parámetros “Coliformes totales, Coliformes fecales y Escherichia Coli” para determinar el estado microbiológico en el que se encuentran los vertidos provenientes de la planta de tratamiento de aguas residuales del Cantón El Guabo. Por medio de varias técnicas e instrumentos de investigación como la observación, entrevistas a varias autoridades de EPAAGUA Y DGA, se pudo optimar el diagnóstico. Como diagnostico final se determinó que la estructura de la planta de tratamiento no cumple totalmente su función en cuanto la depuración de las aguas debido a que la capacidad no abastece al número de familia del sitio, el tratamiento no está funcionando para los parámetros microbiológicos, excediendo en Coliformes fecales con 2,5 veces, Coliformes Totales con 24,097 veces, sin embargo, con la Escherichia Coli se encuentra dentro del rango. Tomando en cuenta el Texto Unificado de Legislación Secundaria del Medio Ambiente, Norma De Calidad Del Agua Y Control De Descargas AG-CC-01 de la Republica dominicana y Régimen Jurídico de la Reutilización de las Aguas Depuradas de España. Como propuesta integradora se proyectó un posible Diseño de un tanque de cloración / sistema de desinfección como tratamiento final, con el fin de disminuir las cargas microbiológicas. Se propuso un esquema que vaya acorde al área de la planta de tratamiento y la cantidad del caudal residual, además del tiempo de retención que va a tener el agua residual así disminuyendo los LMP, obteniendo como producto final una agua tratada y libre de contaminación.
Keywords: AGUA RESIDUAL; DIAGNOSTICO AMBIENTAL; PLANTA DE TRATAMIENTO